The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jcma.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thrombophilia and recurrent pregnancy loss in patients with polycystic ovary syndrome: A comparative study

Abstract: Hyperinsulinemia, hyperandrogenemia, hypofibrinolysis, and hyperhomocysteinemia as well as APCR and factor V Leiden mutations are associated with RPL in patients with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…A majority of the thrombophilic defects in women with RPL are in the protein C pathway; thus, a decreased protein C activity has been previously reported in these patients . Hyperandrogenaemia, specifically increased DHEAS, has been associated with RPL in PCOS patients . We have reported in previous studies the association of dysregulated T‐cell immunity, such as increased Th1/Th2 cell ratios in women with RPL and RIF when compared to fertile controls .…”
Section: Discussioncontrasting
confidence: 51%
“…A majority of the thrombophilic defects in women with RPL are in the protein C pathway; thus, a decreased protein C activity has been previously reported in these patients . Hyperandrogenaemia, specifically increased DHEAS, has been associated with RPL in PCOS patients . We have reported in previous studies the association of dysregulated T‐cell immunity, such as increased Th1/Th2 cell ratios in women with RPL and RIF when compared to fertile controls .…”
Section: Discussioncontrasting
confidence: 51%
“…However, thrombophilic defects sometimes occur, and women with thrombophilic defects are at an increased risk for pregnancy-associated thromboembolism and other vascular complications, such as preeclampsia and fetal loss. 8,9 Human plasminogen activator inhibitor-1 (PAI-1) plays a vital role in hypofibrinolysis and thrombotic complications. 10 The PAI-1 gene consists of nine exons, and several polymorphisms within the PAI-1 gene [including the most investigated promoter variants, a PAI-1-675G/A (4G/5G) insertion-deletion and a -844G/A single nucleotide polymorphism (SNP)] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Kazerooni and coworkers, also observed higher levels of Hcy in patients with RPL than in healthy people. 14 In the present study folic acid was given in an oral daily dose of 5mg/day to women of group 1 and in a dose of 0.5mg/day for women of group 2. We found that the effect of folic acid 5mg/day was significant while the effect of folic acid 0.5 mg was non-significant against the occurrence of early recurrent pregnancy loss (p < 0.05).…”
Section: Discussionmentioning
confidence: 92%